Answer:
g(4) = 7 and f(g(4)) = 43
Step-by-step explanation:
First find g:
g(x) = 3x-5
g(x) = 3(4) - 5
g(x) = 12 - 5
g(x) = 7
Plug in:
f(g(4))
f(7)
Now, find f:
7^2 - 7 + 1
49 - 7 + 1
42 + 1
f(x) = 43
To solve the problem you must know that to change from Cartesian to polar coordinates you must write:
x = rcos (θ)
Where "r" is the radius
Likewise y = rsin (θ)
Therefore, in the expression r = 3cos (θ) one can write r as:
r = x / cos (θ)
So:
x / cos (θ) = 3cos (θ)
x = 3cos ^ 2 (θ)
The same for y ...
y = rsin (θ)
y = 3cos (θ) sin (θ).
Finally the correct answer is option 2.
x = 3cos ^ 2 (θ) y = 3cos (θ) sin (θ).
Calleigh should put in 30 pennies
Answer: Yes. When you solve your equations, you're solutions will change a little bit. It's good because it'll give you the right answer.
I hope this helps you and I hope it's right. ☺
Step-by-step explanation:
Let the breadth (b) of a rectangle be x
Then Length (L) = 2x
Now
Perimeter of the rectangle = 15 inches
Or, 2(L + b) = 15
2 ( 2x + x) = 15
2* 3x = 15
6x = 15
x = 15 / 6
x = 2.5 inch
Also Now
Length (L) = 2*2.5 = 5 inches
Breadth (b) = 2.5 inches
Hope it will help :)